Evaluation of vigor of corn seeds by accelerated aging test - Scotti, Carlos Alberto; Godoy, Osvaldo Pereira (Pesquisa Agropecuaria Brasileira, 2014)
Seeds of three different sizes of four corn cultivars ('Ag-152', 'Hmd-7974', 'Centralmex’ and 'Cateto') were studied for vigor, by employing of three accelerated aging periods. The evaluation was made through germination tests in the laboratory and by the speed of emergence in the field. Large sized seeds showed significantly higher percentage of germination. Differences in vigor in laboratory as well as field tests were observed between varieties. Specific studies on period of aging for different cultivars are indicated.